PELATIHAN PEMBUATAN SAOS TOMAT PADA KELOMPOK PEKARANGAN PANGAN LESTARI NGONGAK TANDURAN - Dian Ardifah Iswari; Santosa Pradana Putra Setya Negara; Irfan Miftahul Fauzi; Ihwan Susila; Sherly Oktaviana Putri; Kilau Mustika Bayu Aji (Universitas Merdeka Madiun, 2023)
Ngongak Tanduran Sustainable Food Farm (P2L) is a business group engaged in cultivating and selling fresh vegetables from their own plants. The problem experienced by P2L Ngongak Tanduran is difficulty cultivating tomatoes. The tomatoes produced are of poor quality, so they cannot be sold. This is certainly detrimental for P2L Ngongak Tanduran, because cultivating tomatoes requires quite a lot of money. To overcome the problems at P2L Ngongak Tanduran, training in making tomato sauce was carried out. Training on making tomato sauce was carried out in two stages, namely socialization of tomato derivative products and training on making tomato sauce. Socialization activities were carried out to find out how far P2L Ngongak Tanduran understands about derivative products. The method used is giving questionnaire questions to the training participants. The second activity, namely making tomato sauce, was carried out by directly teaching the training participants how to make tomato sauce. The result of this community service activity is that training participants who previously did not understand what is meant by tomato derivative products now understand what is meant by tomato derivative products. The second result is that the training participants become able to make tomato sauce independently. The conclusion obtained from the implementation of this training was that the training participants were very enthusiastic and felt very happy because they got solutions to the problems that occurred.Ngongak Tanduran Sustainable Food Farm (P2L) is a business group engaged in cultivating and selling fresh vegetables from their own plants. The problem experienced by P2L Ngongak Tanduran is difficulty cultivating tomatoes. The tomatoes produced are of poor quality, so they cannot be sold. This is certainly detrimental for P2L Ngongak Tanduran, because cultivating tomatoes requires quite a lot of money. To overcome the problems at P2L Ngongak Tanduran, training in making tomato sauce was carried out. Training on making tomato sauce was carried out in two stages, namely socialization of tomato derivative products and training on making tomato sauce. Socialization activities were carried out to find out how far P2L Ngongak Tanduran understands about derivative products. The method used is giving questionnaire questions to the training participants. The second activity, namely making tomato sauce, was carried out by directly teaching the training participants how to make tomato sauce. The result of this community service activity is that training participants who previously did not understand what is meant by tomato derivative products now understand what is meant by tomato derivative products. The second result is that the training participants become able to make tomato sauce independently. The conclusion obtained from the implementation of this training was that the training participants were very enthusiastic and felt very happy because they got solutions to the problems that occurred.